Association between triglyceride-glucose index and thyroid function in euthyroid adults: The Korea National Health and Nutritional Examination Survey 2015. - Wonsuk Choi (Public Library of Science (PLoS), 2021)
Objectives Low-normal thyroid function is associated with numerous metabolic risk factors including insulin resistance (IR). Triglyceride-glucose (TyG) index is a new surrogate marker of IR calculated by fasting triglyceride and glucose levels. Here, we investigated the association between thyroid function and TyG index in non-diabetic euthyroid adults. Methods This cross-sectional study was based on data from the Korean National Health and Nutritional Examination Survey 2015 including 1482 individuals (741 men and 741 women). Serum thyrotropin (TSH) and free thyroxine (fT4) levels were measured. Results After adjusting for confounders, there was an inverse relationship of TyG index with fT4 in men (β = -0.094, P = 0.009) and a positive relationship of TyG index with TSH in women (β = 0.078, P = 0.018). The lowest fT4 tertile in men (P = 0.001) and the highest TSH tertile in women (P = 0.010) exhibited increased TyG index after adjusting for confounders. The lowest fT4 tertile also showed increased homeostatic model assessment for IR (HOMA-IR) only in men (P = 0.006). Odds ratios (ORs) for the high TyG index, which was defined as the highest TyG quartile decreased in the highest and second highest tertile of fT4 in men (OR = 0.41 and OR = 0.45, respectively; P < 0.001) and increased in highest tertile of TSH in women (OR = 1.81, P = 0.031) after adjusting for confounders. The OR for high HOMA-IR defined as the highest HOMA-IR quartile was also lower in the highest and second highest fT4 tertiles in men (both OR = 0.47; P = 0.003). Conclusions This is the first study to suggest that TyG index is a good surrogate marker of IR in evaluating its relationship with thyroid function.